2017
DOI: 10.3390/app7080778
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Crotamiton from Reverse Osmosis Concentrate by a TiO2/Zeolite Composite Sheet

Abstract: Abstract:Reverse osmosis (RO) concentrate from wastewater reuse facilities contains concentrated emerging pollutants, such as pharmaceuticals. In this research, a paper-like composite sheet consisting of titanium dioxide (TiO 2 ) and zeolite was synthesized, and removal of the antipruritic agent crotamiton from RO concentrate was studied using the TiO 2 /zeolite composite sheet. The RO concentrate was obtained from a pilot-scale municipal secondary effluent reclamation plant. Effective immobilization of the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Similar adsorption of crotamiton by the RAOC in the RO concentrate base tests compared with the ultrapure water base tests demonstrated that the coexisting matter in the RO concentrate (Exhibit 1) had no effect under the experimental condition. Similar results on the treatment of crotamiton using just the HSZ‐385/P25 composite sheet were obtained in another study (Xiang et al., 2017b).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Similar adsorption of crotamiton by the RAOC in the RO concentrate base tests compared with the ultrapure water base tests demonstrated that the coexisting matter in the RO concentrate (Exhibit 1) had no effect under the experimental condition. Similar results on the treatment of crotamiton using just the HSZ‐385/P25 composite sheet were obtained in another study (Xiang et al., 2017b).…”
Section: Resultssupporting
confidence: 85%
“…As shown in Exhibit 7, of the three types of treatment, the lowest amount of degradation intermediates resulted from the treatment of crotamiton using the RAOC. In another report, it was confirmed that the degradation intermediates can be captured on the composite sheet through adsorption (Xiang et al., 2017b). The RAOC could similarly mitigate the negative effect of harmful degradation intermediates produced by advanced oxidation processes.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Reverse osmosis (RO) concentrate from wastewater reuse facilities contains concentrated emerging pollutants, such as pharmaceuticals [16]. In an article entitled "Removal of Crotamiton from Reverse Osmosis Concentrate by a TiO 2 /Zeolite Composite Sheet", Xiang et al [17] assessed the removal of the antipruritic agent crotamiton from RO concentrate using a TiO 2 /zeolite composite sheet. The TiO 2 /zeolite composite sheet showed excellent performance for crotamiton adsorption without obvious inhibition by other components in the RO concentrate.…”
Section: Removal Of Trace Organic Contaminantsmentioning
confidence: 99%